Innovative Zein-derived inks: Towards sustainable 3D printing solutions - Derniza-Elena Cozorici; Erika Blanzeanu; Ionut-Cristian Radu; Marian Nicolae Verziu; Cristina Stavarache; Minodora Marin; Rafael Luque; Catalin Zaharia (Results in Engineering)
The demand for sustainable materials has become increasingly critical with the rapid expansion of 3D printing technologies. This study highlights the development of a biodegradable, zein-based bio-ink derived from corn gluten meal as a promising candidate for extrusion-based 3D printing applications. A novel two-step functionalization strategy was employed, involving the esterification of zein to introduce hydroxyl groups, followed by methacrylation with methacrylic acid to create a UV-curable ink formulation. The functionalization was validated through ¹HNMR and FTIR analyses, and the photocrosslinking potential was demonstrated in a UV-curing chamber. Rheological analysis confirmed the shear-thinning behavior of the ink, with optimized viscosity ensuring smooth extrusion and shape fidelity. Mechanical testing of UV-crosslinked constructs revealed a solid-like structure with a storage modulus (Gʹ) exceeding the loss modulus (Gʺ) by an order of magnitude, indicating strong elastic properties and structural stability. The optimized ink formulation achieved excellent printability with up to 90 %-dimensional accuracy and robust mechanical properties, making it suitable for biomedical applications. These findings expand the limited research on zein as a 3D-printable material, showcasing its potential for sustainable manufacturing and soft tissue engineering.